Improving junior high school students' critical thinking skills through an ethnomathematics-based problem-based learning model with the teaching at the right level approach - Irham Taufiq; Agus Maman Abadi; Ariyadi Wijaya; Istiqomah Istiqomah; Nafi’ah Rahma Utami (Bulletin of Educational Management and Innovation, 2026)
Background: Although previous studies have examined ethnomathematics, Problem-Based Learning (PBL), and the Teaching at the Right Level (TaRL) approach separately, empirical evidence on their integrated application in mathematics learning remains scarce. This study addresses this gap by evaluating the effectiveness of an ethnomathematics-based PBL model integrated with the TaRL approach to enhance junior high school students' critical thinking skills. Purpose: This study aims to compare the effectiveness of the ethnomathematics-based Problem-Based Learning (PBL) model integrated with the Teaching at the Right Level (TaRL) approach and the conventional PBL model in improving the critical thinking skills of seventh-grade junior high school students. Method: The study adopted a quantitative quasi-experimental approach and utilized a pretest–posttest control group design. This study employed cluster random sampling because the population consisted of intact seventh-grade classes. Rather than randomly selecting individual students, two existing classes were randomly selected from the population. One class (VII D; n = 28) was assigned as the experimental group, while another class (VII E; n = 29) served as the control group. Data were obtained through pre-intervention and post-intervention tests, observation records, and relevant documentation. To address the research objectives, the data were analyzed using descriptive and inferential statistical procedures, whereas hypothesis testing was performed using the Independent Samples t-test to determine the significance of differences between groups.  Findings: Findings: Students taught using the ethnomathematics-based Problem-Based Learning (PBL) model integrated with the Teaching at the Right Level (TaRL) approach obtained a higher mean critical thinking score (M = 49.58) than students taught using the PBL model without ethnomathematics and TaRL (M = 32.64). The difference was statistically significant (p = 0.006) and showed a moderate effect size (Cohen's d = 0.84), indicating that the integrated instructional model was more effective in improving seventh-grade junior high school students' critical thinking skills. The novelty of this study lies in integrating ethnomathematics-based PBL with the TaRL approach into a single instructional framework that combines culturally contextualized mathematics learning with differentiated instruction based on students' learning readiness